Animal creativity and innovation - Kaufman, Allison B.; Kaufman, James C. (London ; San Diego, CA : Academic Press/Elsevier, 2015)
"Animal Creativity and Innovation explores theories and research on animal innovation and creativity, comparing and contrasting it with theory and research on human creativity and innovation. In doing so, it encompasses findings from psychology, biology, neuroscience, engineering, business, ecology, and education. The book includes examples of animal innovation in parrots, dogs, marine mammals, insects, and primates, exploring parallels from creative play in children. The book defines creativity, differentiating it from play, and looks at evolutionary models and neurological constructs. The book further explores applied aspects of animal innovation and creativity including tool use and group dynamics, as well as barriers to creativity. The final chapters look into how creative behavior may be taught or trained. Each chapter is followed by a commentary for integration of thoughts and ideas between animal and human research, behavioral and cognitive research, and theory and observation in real life."--Provided by publisher.
III. The struggle for creativity : Brain size and innovation in primates / Ana Navarrete and Kevin Laland : Primate innovation ; Costs of innovation ; Primate brain evolution ; Brain measures ; Costs of encephalization ; New perspectives ; Commentary : Innovation and the value of building on what we know / Thomas B. Ward -- Minding the gap: a comparative approach to studying the development of innovation / Jackie Chappell, Nicola Cutting, Emma C. Tecwyn, Ian A. Apperly, Sarah R. Beck and Susannah K.S. Thorpe : Why is innovation important? ; Approaches to studying innovation ; Components of innovation ; Ill-structured problems ; Commentary : Minding the gap: problem construction and ill-defined problems / Roni Reiter-Palmon -- Necessity, unpredictability and opportunity: an exploration of ecological and social drivers of behavioral innovation / Phyllis C. Lee and Antonio C. de A. Moura : Unpredictability ; Innovation in capuchin tool use ; Social skill innovation ; Commentary : Necessity, unpredictability, opportunity, and creativity / Marie J.C. Forgeard and Eranda Jayawickreme -- Cognitive and noncognitive aspects of social learning / Thomas R. Zentall : Social influence ; Simple learning in the context of social cues ; The social learning of behavior ; Possible behavioral and biological mechanisms ; Possible biological mechanisms ; Commentary : Imitation and creativity / John Baer -- Of course animals are creative: insights from generativity theory / Robert Epstein : Those amazing animals ; Animal art ; Generativity ; Commentary : Defining animal creativity: little-c, often; big-C, sometimes / Dean Keith Simonton -- IV. Pushing the boundaries of creativity : Conservatism versus innovation: the great ape story / Josep Call : Problem solving and inhibitory control ; Social learning and social traditions ; Individual and contextual differences ; Conservatism, social conformity, and cumulative culture ; Two directions for future research ; Commentary : Conservatism versus innovation: the great ape story / Weihua Niu -- Tools for the trees: orangutan arboreal tool use and creativity / Anne E. Russon, Purwo Kuncoro and Agnes Ferisa : Background ; This study ; Methods ; Results ; Discussion ; Conclusion ; Appendix A. Catalog: tools orangutans use in arboreal travel and positioning ; Commentary : Tools for the trees: orangutan arboreal tool use and creativity / David H. Cropley -- Insects as a model system to understand the evolutionary implications of innovation / Emilie Snell-Rood, Eli Swanson and Sarah Jaumann : Defining innovation from an evolutionary perspective and incorporating "mistakes" ; Resource search in insects: the role of trial-and-error processes ; Host shifts and diversification: behavioral innovation leads the way ; The spread of innovations through social interactions ; Conclusions and implications ; Commentary : Insect creativity as applied to human organizational behavior: a form of social biomimicry? / Samuel T. Hunter -- Creating creative animals / Karen Pryor : About "anecdotal" observation ; Spontaneous creativity ; Modern, marker-based training ; Creative training precursors ; Creativity in the wild ; Commentary : Creating creative animals / James C. Kaufman -- Animal creativity and innovation: an integrated look at the field / William J. O'Hearn, Allison B. Kaufman and James C. Kaufman.
Includes bibliographical references and index.
Online resource; title from e-book title screen (EBL platform, viewed July 1, 2016).
Keywords: Animal intelligence; Creative ability; Psychology, Comparative; PSYCHOLOGY -- Applied Psychology; SELF-HELP -- Personal Growth -- General; SELF-HELP -- Personal Growth -- Happiness; SELF-HELP -- Personal Growth -- Success; Animal intelligence; Creative ability; Psychology, Comparative; Electronic books; Electronic books